Bringing Cardiovascular Comorbidities in Acromegaly to an Update. How Should We Diagnose and Manage Them? - Ramos-Leví, Ana M.; Marazuela, Mónica (Frontiers in Endocrinology, 2019)
Patients with acromegaly frequently develop cardiovascular comorbidities, which significantly affect their morbidity and contribute to an increased all-cause mortality. In this regard, the most frequent complications that these patients may encounter include hypertension, cardiomyopathy, heart valve disease, arrhythmias, atherosclerosis and coronary artery disease. The specific underlying mechanisms involved in the pathophysiology of these comorbidities are not always fully understood, but uncontrolled GH/IGF-I excess, age, prolonged disease duration, and coexistence of other cardio-vascular risk factors have been identified as significant influencing predisposing factors. It is important that clinicians bear in mind the potential development of cardiovascular comorbidities in acromegalic patients, in order to promptly tackle them, and avoid the progression of cardiac abnormalities. In many cases, this approach may be performed using straightforward screening tools, which will guide us for further diagnosis and management of cardiovascular complications. This article focuses on the most prevalent cardiovascular comorbidities and their pathophysiology in acromegalic patients and aims to address recommendations for their diagnosis, management and treatment.